Rainfall Anomaly and Its Effect on the Clove Productivity in Two Regions with Different Rain Pattern In Maluku - Manullang, Sovya M M; Laimeheriwa, Samuel; Amba, Martha (JURNAL BUDIDAYA PERTANIAN, 2023)
Clove production in Maluku fluctuates from year to year, one of which is influenced by rainfall anomalies. This study aimed of describing extreme rainfall events and analyzing the relations between rainfall and clove productivity in two areas with different rainfall patterns in Maluku. This study used a survey method by using interviews and Focus Group Discussions with several farmer respondents as well as collecting climatic data from related agencies. Data analysis was divided into rainfall data generation, rainfall analysis in extreme conditions, and regression analysis to assess the effect of rainfall on clove productivity. The results showed that a very extreme El Nino event caused a decrease in rainfall on Nusalaut Island by 1868 mm or 57% of its normal condition, and in Air Buaya District by 875 mm or 42% of its normal condition. Very extreme La Nina events caused rainfall to increase in Nusalaut Island by 2059 mm or 62% of its normal condition, and in Air Buaya District by 1193 mm or 37% of its normal condition. The results of the regression analysis showed that the value of the coefficient of determination (R²) for Nusalaut Island by 84.8% and for Air Buaya District by 70.8%; this shows that rainfall has a significant effect on clove productivity.